Improving Student Academic Performance Through Web Base Learning - Supratman Zakir; Efmi Maiyana; Phaosan Jehwae (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The development of digital technology has triggered changes in the way people learn in various educational institutions, both formal and informal. The development of digital technology has encouraged students to improve their academic performance or learning achievements. Several problems, however, can arise, from the gap in the ability of students to master digital technology, the ability to provide technological infrastructure, the competence of top-level management and the ability of the IT department to determine the success of digitalization. One learning model that can be utilized in physical distancing policy is Web-Based Learning (WBL). WBL is a learning model that can be used without limitation of time, space, and learning resources. WBL was developed by using the Research and Development (RnD) with a 4D (Define, Design, Develop, Disseminate) approach. To develop WBL products, we used the unified modeling language (UML), flowcharts, and context diagrams. The product was tested which included product validity testing, practicality testing, and product effectiveness testing. The testing results showed that the product was valid, practical, and effective to be used as a guide for developing and implementing WBL in order to improve students' academic performance.